2017
DOI: 10.1016/j.micpro.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

AxleDB: A novel programmable query processing platform on FPGA

Abstract: With the rise of Big Data, providing high-performance query processing capabilities through the acceleration of the database analytic has gained significant attention. Leveraging Field Programmable Gate Array (FPGA) technology, this approach can lead to clear benefits. In this work, we present the design and implementation of AxleDB: An FPGA-based platform that enables fast query processing for database systems by melding novel database-specific accelerators with commercial-off-the-shelf (COTS) storage using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Recently, hardware accelerators, such as FPGAs and GPUs, have also been considered a viable alternative to modern CPUs for accelerating common relational operators [36,57], including selections [32,72]. FPGAs are either integrated into a datapath between a network and processor to perform database operations [1,65,79], viewed as a co-processor or accelerator [20], or domain-specific processors [21,53,57,69]. Similarly, GPUs have also demonstrated significant speed-up in data processing [12,24,70] by proposing kernel scheduling, algorithms, and data structures to overcome architectural challenges like avoiding thread divergence and offering coalesced memory access pattern.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, hardware accelerators, such as FPGAs and GPUs, have also been considered a viable alternative to modern CPUs for accelerating common relational operators [36,57], including selections [32,72]. FPGAs are either integrated into a datapath between a network and processor to perform database operations [1,65,79], viewed as a co-processor or accelerator [20], or domain-specific processors [21,53,57,69]. Similarly, GPUs have also demonstrated significant speed-up in data processing [12,24,70] by proposing kernel scheduling, algorithms, and data structures to overcome architectural challenges like avoiding thread divergence and offering coalesced memory access pattern.…”
Section: Related Workmentioning
confidence: 99%
“…Embedding reconfigurable hardware in storage devices is a growing area of interest [6,33,43,65]. For instance, Ibex [79] is a MySQL accelerator platform where a SATA SSD is coupled with an FPGA.…”
Section: Related Workmentioning
confidence: 99%
“…In comparison to traditional general-purpose CPU-based systems, hardware accelerators provide better power, performance, and energy efficiency in various domains such as database processing [35], [36], [37], speech recognition [38], [39], [40], and neural network applications [14], [41]. However, with the rise of the size of data, energy consumption is still a key concern.…”
Section: Related Workmentioning
confidence: 99%
“…Near-storage processing augments the storage device with a computation offload engine, which both adds computation capacity as well as reduces the data transported over the interconnect. Many previous research have shown great performance benefits, often orders of magnitude improvements over analytics software running purely on the host CPU [9,12,14,18,22,24].…”
Section: Introductionmentioning
confidence: 99%